WOMEN'S ACCESS TO JUSTICE: BEST PRACTICES FROM EUROPEAN UNION COUNTRIES (World Bulletin of Management and Law, 2024)
Accessing justice is an entitlement but women often encounter significant obstacles when trying to exercise this right. This piece delves into the hurdles women face in seeking justice and highlights strategies employed by European Union nations to overcome these challenges. By examining frameworks local initiatives and real life examples the article underscores the value of gender tactics, legal assistance, specialized courts and awareness campaigns, in enhancing women’s access to justice. The research underscores the importance of an cooperative approach involving governments civil society groups and international bodies to empower women in utilizing their right to justice and advancing gender equality
Keywords: Women's access to justice; uropean Union best practices; Gender equality